Identification of Odorant-Binding Proteins (OBPs) and Functional Analysis of Phase-Related OBPs in the Migratory Locust - Guo, Wei; Ren, Dani; Zhao, Lianfeng; Jiang, Feng; Song, Juan; Wang, Xianhui; Kang, Le (Frontiers in Physiology, 2018)
Olfactory plasticity, which is one of the major characteristics of density-dependent phase polyphenism, plays critical roles in the large-scale aggregation formation of Locusta migratoria. It is still unknown whether odorant-binding proteins (OBPs) are involved in phase-related olfactory plasticity of locusts, despite the confirmed involvement of several types of olfactory perception genes. In this study, we performed a large-scale search for OBPs and verified their expression patterns in the migratory locust. We identified 17 OBPs in the L. migratoria genome, of which ten were novel, and we found their scattering distribution characteristics by mapping the genomic loci. Next, we revealed that these OBPs with close phylogenic relationships displayed similar tissue-specific expression profiles by a combined analysis of qRT-PCR and phylogenetic tree reconstruction. In all identified locust OBPs, seven OBPs showed differential mRNA expression levels in antenna tissue between gregarious and solitarious nymphs. Six of these seven OBPs displayed higher mRNA expression in the antennae of gregarious nymphs. The mRNA expression of LmigOBP2 and LmigOBP4 increased during gregarization and decreased during solitarization. RNAi experiments confirmed that only LmigOBP4 regulates the behavioral traits to affect gregarious behavior. These results demonstrated that OBPs might play important roles in the regulation of phase-related behaviors of the migratory locust.